The shear strength of soft clay reinforced with single crushed brick column - Oh, Chun Wei (2018)
Soft Clay is often known to be a problematic soils in construction because of its low strength and high compressibility characteristic. Before construction begins, ground improvement needs to be done to improve the soil bearing capacity so that the superstructure can be placed on top of it and reduce settlement and consolidation. In this study, the soft clay is going to be reinforced with crushed brick column which is part of construction waste produced during construction stage to achieve sustainable construction. This study was aimed to investigate the effectiveness of single crushed brick column in improving the shear strength by using laboratory scale model. Kaolin is being used as soil sample while crushed brick as the reinforced column. Few laboratory tests are conducted to determine the properties of kaolin clay and crushed brick. Unconfined Compression Test (UCT) also used to test the shear strength of the reinforced kaolin samples. The dimension of the specimen used is 50mm in diameter and 100mm in height and a total 3 batches of kaolin samples were tested and each batch contains control sample and samples reinforced with 10mm and 16mm with different column penetration ratio. There are two different types of diameter of single crushed brick column used in this study which are 10mm and 16mm. The heights of the column installed into soft clay are 60mm, 80mm and 100mm. The improvement of shear strength of single crushed brick column with area replacement ratio of 4.00% (10mm column diameter) are 3.34%, 4.60% and 1.07% at sample penetration ratio, Hc/Hs of 0.6, 0.8 and 1.0 respectively while for area replacement of 10.24% (16 mm column diameter) are 7.56%, %, 16.37% and 4.97% at the same penetration ratio. It can be concluded that the shear strength of soft clay could be improved by installation of single crushed brick column.